2014
DOI: 10.1063/1.4895707
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected ferromagnetic ordering enhancement with crystallite size growth observed in La0.5Ca0.5MnO3 nanoparticles

Abstract: In this paper, the physical properties of half-doped manganite La0.5Ca0.5MnO3 with crystallite sizes ranging from 15 to 40 nm are investigated. As expected, ferromagnetic order strengthens at expense of antiferromagnetic one as crystallite size is reduced to 15 nm. However, contrary to previously reported works, an enhancement of saturation magnetization is observed as crystallite size increases from 15 to 22 nm. This unexpected behavior is accompanied by an unusual cell volume variation that seems to induce f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…43,44 Earlier, Iniama et al reported on the particle size dependence of LCMO5 on coercivity. 45 They reported that coercive field is negligible for bulk samples, whereas with decreasing particle size, coercivity enhances.…”
Section: B Magnetization and Thermoelectric Power Studiesmentioning
confidence: 99%
“…43,44 Earlier, Iniama et al reported on the particle size dependence of LCMO5 on coercivity. 45 They reported that coercive field is negligible for bulk samples, whereas with decreasing particle size, coercivity enhances.…”
Section: B Magnetization and Thermoelectric Power Studiesmentioning
confidence: 99%
“…Electronic phase separation (EPS), is a signature phenomenon of LSMO, LCMO and LPCMO, where both ferromagnetic‐metal and paramagnetic‐insulator phases can coexist . Depending on the composition, EPS typically occurs at the mesoscale (500–800 nm), but nanoscale EPS is also reported, arising from the interplay between cation inhomogeneities and long‐range Coulomb interactions . For a uniform cation distribution, the EPS length scale is of the order of 5–10 ideal perovskite unit cell parameters ((001) c lattice spacing), in agreement with our observations of ca.…”
Section: Resultsmentioning
confidence: 99%
“…Manganites further exhibit a complex magnetic and magnetotransport behavior that can be tuned by appropriate substitution on the A site of the perovskite or by adjusting the size of the particles. This has translated into diverse studies in magnetism and magnetotransport in general …”
Section: Introductionmentioning
confidence: 99%
“…The magnetic contribution from surface disorders can be safely excluded. Thus the possible mechanism of exchange coupling between AFM core and spin glass like surface can be excluded 10 18 40 41 42 43 . Furthermore, the ME induced weak ferromagnetic moment in the particle core might also be pinned by the disordered surface spins 44 45 .…”
Section: Discussionmentioning
confidence: 99%